Integration of the Pyrolysis Context with the Heat Module to Improve Students' Mastery of Concepts - Nofita, Inka; Mayub, Afrizal; Johan, Henny (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2025)
The energy crisis due to declining fossil fuel reserves and the increase in organic waste, such as coffee husk waste in Kepahiang Regency, has prompted the need for renewable energy-based solutions. This research aims to develop a science learning module based on the local context through the integration of the concept of pyrolysis of coffee husk waste in the heat and its displacement material. The research method uses the ADDIE model until the validation stage. Data were collected through needs questionnaires and expert validation sheets, analyzed descriptively. The results showed the low interest and understanding of students in the caloric material, as well as the dominance of textual learning methods without direct practice. Most students stated the need for modules that are visual, contextual, and easy to understand. The modules developed are declared valid by experts from the material, linguistic, and graphic aspects. In conclusion, the integrated heat module for coffee skin waste pyrolysis is considered feasible as an innovative teaching material on the concept of heat contextually and applicatively.